Accounting for Digital Currency: Preliminary Evidence From Malaysia - Yap, Angeline Kiew Heong; Yap, Saw Teng (European Publisher, 2019)
The increasing popularity in digital currency usage is pressuring accountants to undertake stewardship in recognizing, measuring and disclosing its transaction. Despite the increased usage, there is still a lack of guidelines in the international accounting standards resulting in accounting treatment variation for digital currency transactions. A few existing accounting standards were considered depending on the situations whether one receives, issues or trades the currency. The objective of this paper is to survey the accounting of digital currency using stewardship and neoliberalism principles. Neoliberalism requires a shift towards reporting which emphasises on “faithful representation” in providing useful information to users. This paper analysed data received from 173 accounting and finance experts working in various industries. For the application of stewardship in accounting, “Carrying amount of digital currency should be tested for impairment” scored the highest mean of 4.47, followed by “Accounting needs to reflect the future cash flow inherent in the digital currency” (mean = 4.34) and “Digital currency is recognised when there is an objective control evidence” (mean = 4.31). Neoliberalism requires a transaction to be accounted for the future application using fair value measurement. “Volatility in the digital currency’s price must be made known to users” scored a highest mean of 4.43, followed by “Emphasis should be placed on accounting the economic substance of the digital currency (mean = 4.38). The findings of this paper contribute to the literature by offering views to the standard setters and professional bodies to explore applicable accounting treatments for the digital currency.